Evaluation of the PPL-MBKM Program in the Islamic Education Study Program at Universitas Muhammadiyah Luwuk - Abute, Erniwati La; Rasyid, Muhammad Nur Akbar (Riwayat: Educational Journal of History and Humanities, 2025)
This article aims to evaluate the implementation of the PPL-MBKM program of the PAI study program of the University of Muhammadiyah Luwuk. This study uses a qualitative approach and a type of CIPP model evaluation research through descriptive analysis, data collection process through interviews, observation and documentation. The results of this study show that in the context aspect, the goals of PPL-MBKM have mostly referred to the curriculum structure and guidelines based on Core Competencies. In terms of input, it has been implemented according to the demands of the curriculum. At the process stage, it is in the category of quite good, because starting from the debriefing activities, to the competencies possessed by the DPL and the committee are in accordance with the standards. The evaluation at the product stage is in the medium category, because the condition of the interns is not optimal. However, overall the implementation of the PPL-MBKM program in the PAI Study Program of the University of Muhammadiyah Luwuk has been good, although there are still shortcomings that must be corrected. It can be concluded that the evaluation of the CIPP model can be used to make improvements as well as develop the implementation of the PPL-MBKM program in the next period.